Pembinaan Kesejahteraan Psikologis Warga Binaan melalui Workshop Konseling di Lapas Kelas III Rangkasbitung - Lafiola, Slavina; Mutaqin, Moh Fikri Tanzil (Al-DYAS, 2025)
This study is motivated by the critical role of correctional institutions (Lembaga Pemasyarakatan) in fostering the rehabilitation of inmates not only from a legal perspective but also in terms of psychological well-being. The aim of this research is to describe the implementation and impact of a counseling workshop on the psychological well-being of inmates at Lapas Kelas III Rangkasbitung. The study employed a descriptive qualitative method, with data collected through observation, interviews, and documentation. The workshop was conducted in one day at the prison hall by students of the Nonformal Education and Guidance and Counseling Program at Universitas Sultan Ageng Tirtayasa, consisting of four main sessions: material delivery, completion of the DASS questionnaire, art therapy through drawing activities, and a reflective spin wheels game. The findings indicate that the workshop enhanced inmates’ understanding of mental health and reduced levels of depression, anxiety, and stress. Moreover, inmates’ active participation had a positive effect on stress management, increased future-oriented hope, and strengthened motivation for personal transformation. These results suggest that counseling workshops are an effective and relevant psychological development strategy that should be implemented sustainably within correctional facilities to support the psychological well-being of inmates.